N6-methyladenosine modification of MEF2A weakens cetuximab sensitivity in colorectal cancer via PD-L1/SOX12 axis - Cao Gao; Jiajia He; Jiemin Zhao; Xuefeng Ni; Yanjie Xu (Cell Death Discovery)
Abstract Colorectal cancer (CRC) treatment is still a challenge due to chemoresistance. We explored MEF2A function and underlying mechanism on cetuximab sensitivity in CRC. In this study, cancer tissues and adjacent non-cancerous samples were harvested from CRC patients. Cell viability, proliferation and apoptosis in CRC cells were tested by CCK-8, EdU, colony formation, and flow cytometry assays. The binding of MEF2A on the PD-L1 promoter was validated using luciferase reporter assay, CHIP, and EMSA, while the relationship of PD-L1 and SOX12 mRNA, as well as RBM15/IGF2BP1 and MEF2A mRNA, was verified by RIP, RNA pull-down, or FISH combined with immunofluorescence. m6A modification level of MEF2A mRNA was assayed by MeRIP. The expressions of key genes and proteins, including MEF2A, PD-L1, SOX12, RBM15, IGF2BP1, apoptosis- and cell cycle-related proteins, were determined with RT-qPCR, western blot, or immunohistochemistry. In vivo function of MEF2A was validated by establishing a xenograft nude mice model. The results showed that MEF2A was increased in CRC cells and tissues, while it was higher in cetuximab-resistant CRC tissues. Silencing MEF2A improved the sensitivity of cetuximab in CRC cells and xenograft mice. MEF2A binds to PD-L1 promoter to transcriptionally upregulate PD-L1 expression. Increased cetuximab sensitivity was observed in PD-L1 knockout (KO) CRC cells. PD-L1 overexpression reversed the enhanced cetuximab sensitivity induced by MEF2A knockdown. PD-L1 binds to SOX12 mRNA to stabilize its expression. PD-L1 knockdown augmented cetuximab sensitivity, which was overturned by SOX12 overexpression. The m6A modification mediated by RBM15/IGF2BP1 upregulated MEF2A expression in cetuximab-resistant CRC tissues. In conclusion, m6A-modified MEF2A alleviated cetuximab sensitivity in CRC via PD-L1/SOX12 mRNA axis, indicating that MEF2A might function as a promising therapeutic target against cetuximab-resistant CRC.